The Implications of Sociocultural Theory for Islamic Education: A Case Study of Pesantren Ramadhan - Mandala Putra, Fahmi; Suryana, Ermis; Harto, Kasinyo (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2025)
The Sociocultural Learning Theory proposed by Lev Vygotsky guides educators to pay attention to students’ environments and cultural backgrounds in the learning process. This approach aims to make the internalization of learning more effective and meaningful. The implementation of Pesantren Ramadhan activities in Islamic Religious Education (IRE) implicitly reflects the application of this theory. This study employs a qualitative approach with a case study focus. Data were collected through direct observation, in-depth interviews, and documentation. The research subjects included students, teachers, and organizers of the Pesantren Ramadhan program. The findings indicate that the Pesantren Ramadhan activities embody the principles of sociocultural theory. The tilawah (Qur’anic recitation) activity was conducted by empowering peers as facilitators. Discussions and public lectures emphasized social interaction. Various competitions were designed to support students’ Zones of Proximal Development (ZPD). Vygotsky’s sociocultural learning theory is concretely implemented in the Pesantren Ramadhan activities. Its application is evident in the recitation, discussion, and competition activities that reinforce social interaction and foster students' potential development